De Amélia à piriguete: a construção discursiva sobre a mulher nas músicas de MPB e pagode baiano - Paixão, Mislene Carvalho da (2018)
This work aims to analyze how music spreads ideologies about being a woman. In order to do it we will identify the discursive formations about woman in Brazilian Popular Music (MPB) and Pagode from Bahia state. This subject is relevant because it is necessary to problematize the construction of stereotypes about women through discourses reproduced/silenced nowadays about women and their role in the society. For this, two musical genres were analyzed: pagode and MPB, aiming to discuss the way the discourses about femininity circulate in these songs as well as the discursive and ideological formations which permeate the construction of senses. The research also aims to identify the already-said about women materialized in the songs which were analyzed and discuss the notion of music and woman under French Discourse Analysis, especially Pêcheux’s perspective. According to DA, the subject of the discourse is social, historically determined and, therefore, ideologically subjected and also affected by the unconscious, so, subject and sense are constituted in the discourse as the subject takes on in his/her saying/writing the subject-positions from the discourse he/she articulates, which carries marks of the social, historic and ideological. Although, the sense of the word or the image enunciated seems to be evident e, because of this, the necessity of the subject’s interpretation gestures is erased/inconsiderate. So, it is necessary to comprehend the text’s conditions of production (the subjects, the ideology, the memory and the situations). Thus, the music becomes interaction, meaning, a relation between subjects who share a common point of view which defines an object from a similar perspective, in the case of the analyzed song letters, being a woman constitutes a necessary point to a critical reading concerning the image of woman in some musical genres. So, the results of the analysis show that, although women have obtained many achievements in the society, they are still discursed in some song letters as submissive, they are seen as housewives, mothers, who have to take care about the children, husband and chores or even are seen as an object, which serves only for male delight and pleasure.